2021
DOI: 10.21037/tgh.2020.01.11
|View full text |Cite
|
Sign up to set email alerts
|

The value of liquid biopsy in the diagnosis and staging of hepatocellular carcinoma: a systematic review

Abstract: Background: Blood-borne tumour markers in the form of circulating tumour cells (CTCs) are of intense research interest in the diagnostic and prognostic work-up of hepatocellular carcinoma (HCC).Methods: This is a meta-analysis. Using a PICO strategy, adults with HCC was the population, with the individual CTCs as the intervention and comparators. The primary outcome was the sensitivity and specificity of HCC detection with tumour specific single gene methylation alteration. Secondary outcomes were the comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated the feasibility of liquid biopsy to detect mutations and methylation in HCC screening by next-generation sequencing (NGS) [ 21 – 25 ]. Many more studies demonstrated the applicability of single markers or their combination in HCC screening by quantitative polymerase chain reaction (qPCR) and immunoassays [ 26 28 ]. The most representative studies investigated the combination of methylated SEPT9 (mSEPT9) and AFP, which showed significantly higher sensitivity than any single marker alone [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the feasibility of liquid biopsy to detect mutations and methylation in HCC screening by next-generation sequencing (NGS) [ 21 – 25 ]. Many more studies demonstrated the applicability of single markers or their combination in HCC screening by quantitative polymerase chain reaction (qPCR) and immunoassays [ 26 28 ]. The most representative studies investigated the combination of methylated SEPT9 (mSEPT9) and AFP, which showed significantly higher sensitivity than any single marker alone [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many more studies demonstrated the applicability of single markers or their combination in HCC screening by quantitative polymerase chain reaction (qPCR) and immunoassays [ 26 28 ]. The most representative studies investigated the combination of methylated SEPT9 (mSEPT9) and AFP, which showed significantly higher sensitivity than any single marker alone [ 26 28 ]. However, these studies were mostly case-control, and did not reflect the performance of combined markers in screening scenario.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mutant gene responsible for the resistance was present in the circulating tumor DNA (ctDNA) isolated from the peripheral blood samples [ 7 ]. Therefore, it looks plausible to infer tumor biomarkers in the systemic circulation and other liquid biopsies that refer to circulating biomarkers in the form of DNA, RNA, proteins, and metabolites derived from tumors that can give a glimpse into cancer features [ 8 – 10 ]. If the diagnosis of neoplastic growth can be made upfront, the chance of mortality can go down; indeed, disease-free survival is possible in some cancer types, if not all [ 11 ].…”
Section: Introductionmentioning
confidence: 99%